Hospital admission as a deprescribing triage point for patients discharged to Residential Aged Care Facilities. (25th May 2021) - Roberts, Greg; Pegoli, Matthew; Grzeskowiak, Luke; Benger, Sophie; Forbes, Heather; Hunt, Kathryn; Jafari, Shabnam; Koeper, Ivanka; McDonald, Cameron; Nguyen, Hanh; Rawther, Khadeeja; Taeuber, Lauren; et al.
Abstract: Background: Deprescribing may benefit older frail patients experiencing polypharmacy. We investigated the scope for deprescribing in acutely hospitalised patients and the long-term implications of continuation of medications that could potentially be deprescribed. Methods: Acutely hospitalised patients ( n  = 170) discharged to Residential Aged Care Facilities, ≥75 years and receiving ≥5 regular medications were assessed during admission to determine eligibility for deprescribing of key drug classes, along with the actual incidence of deprescribing. The impact of continuation of nominated drug classes (anticoagulants, antidiabetics, antiplatelets, antipsychotics, benzodiazepines, proton pump inhibitors (PPIs), statins) on a combined endpoint (death/readmission) was determined. Results: Hyperpolypharmacy (>10 regular medications) was common (49.4%) at admission. Varying rates of deprescribing occurred during hospitalisation for the nominated drug classes (8–53%), with considerable potential for further deprescribing (34–90%). PPI use was prevalent (56%) and 89.5% of these had no clear indication. Of the drug classes studied, only continued PPI use at discharge was associated with increased mortality/readmission at 1 year (hazard ratio 1.54, 95% confidence interval (1.06–2.26), P  = 0.025), driven largely by readmission. Conclusion: There is considerable scope for acute hospitalisation to act as a triage point for deprescribing in older patients. PPIs in particular appeared overprescribed in this susceptible patient group, and this was associated with earlier readmission. Polypharmacy in older hospitalised patients should be targeted for possible deprescribing during hospitalisation, especially PPIs.